Pengembangan Bahan Ajar Menulis Deskripsi Destinasi Wisata Bengkulu Selatan Berbasis Project-Based Learning Berbantuan Canva - Yuvela Oktiara; Gumono; Abdul Muktadir (UNIB Press, 2026)
This research aims to develop a descriptive writing teaching material integrating South Bengkulu tourism destinations using a Project-Based Learning (PjBL) model supported by Canva. The study also examines the feasibility of the developed material based on expert validation, user responses, and its effectiveness in improving students’ learning outcomes. This development study adopted the ADDIE model involving fifth-grade students and teachers at SD Negeri 52 Bengkulu Selatan. Data were collected through interviews, questionnaires, expert validation sheets, and descriptive writing performance tests. Data analysis employed Aiken’s V, Cohen’s Kappa, percentage eligibility criteria, and N-Gain scores. The results show that (1) the teaching material features contextual content, systematic structure, visual design using Canva, and project-based activities that guide students from observation to producing a final descriptive text; (2) the feasibility assessment by material, language, and design experts yielded a very valid category; (3) teacher and student responses indicated very positive acceptance in terms of clarity, attractiveness, and usefulness; and (4) the material effectively improved learning outcomes with an N-Gain score classified as high. It can be concluded that the Canva-based PjBL teaching material is feasible, practical, and effective for enhancing students’ descriptive writing skills in elementary school.